Chitosan-grafted-poly(aniline-co-anthranilic acid) as a water soluble binder to form 3D structures for Si anodes. Issue 13 (19th February 2020) - Kim, Eunsoo; K. K., Rajeev; Nam, Jaebin; Mun, Junyoung; Kim, Tae-Hyun
Abstract : We develop a polymeric binder with outstanding cell properties, and high water solubility for Si anodes by grafting a conductive PAAA onto chitosan. Abstract : We graft an electrically conductive poly(aniline- co -anthranilic acid) (PAAA) polymer capable of interacting with Si particles onto chitosan, a natural hydrophilic polymer, to form a chitosan- grafted -PAAA (CS- g -PAAA) copolymer, and use it as a new water soluble polymeric binder for Si anodes to relieve the physical stress resulting from Si volume change during charge/discharge cycles. The carboxylic acid functional groups within the PAAA structure, as well as the chitosan functional groups, bind to silicon particles to form a stable 3D network, resulting in high adhesion. Because the binder is conductive, the electrode using the CS- g -PAAA-8 : 1 with an optimal composition ratio of CS to PAAA of 8 : 1 shows a high initial capacity of 2785.6 mA h g −1, and maintains a high capacity of 1301.0 mA h g −1 after 300 cycles. We also extract chitosan directly from crab shells, and fabricate a Si@ECS- g -PAAA electrode by grafting PAAA onto the extracted-chitosan (ECS). This electrode records an initial capacity of 3057.3 mA h g −1, and maintains a high capacity of 1408.8 mA h g −1 with 51.4% retention after 300 cycles. Overall, we develop a polymeric binder with outstanding cell properties, ease of fabrication, and high water solubility for Si anodes by grafting a conductive PAAA onto chitosan.